Literature Review of Science Learning Activities with Integrated STEM Education - Arina Zaida Ilma; Insih Wilujeng; Zuhdan Kun Prasetyo (Future Science, 2022)
Science, Technology, Engineering, and Mathematics (STEM) education has been widely applied in science subjects. Structured in its application needs to be designed clearly, including the learning activities. The research objective is to analyze articles that discuss learning activities that can be carried out by teachers using this approach. The research method used is a literature review adapted from Ramdhani, et al. includes four stages, namely choosing a review topic, finding and selecting articles that match the article, analyzing and synthesizing literature, and arranging review writing. Based on the inclusion criteria, five international articles were selected. The results show that learning science with an integrated STEM can be clearly designed and certainly can connect the disciplines. In designing learning activities, it is necessary to determine topics, identify models, materials, and learning media, determine abilities be explored and learning objectives, also design learning activities and evaluate progress. For further research, can use the STEM approach in science learning empirically in the curriculum, and learning activities can be developed by integrating fields in STEM Education using a learning model or media.